Anterior clinoidal meningiomas: analysis of 43 consecutive surgically treated cases - (:unkn) unknown (SPRINGER WIEN, 2008)
Background. Anterior clinoidal meningiomas are considered different from meningiomas of the medial sphenoid wing, but there is still some confusion about identification. The current classification scheme only considers tumour origin and invasion pattern around the clinoid process as indicators of resectability. However, the size of the tumour has important effects on surgical outcome. The purpose of this study was to analyze our clinical experience with anterior clinoidal meningiomas and refine the current classification scheme. Method. Forty-three consecutive cases of anterior clinoidal meningioma were retrospectively analyzed. All were surgically treated at the Marmara University Department of Neurosurgery, the Marmara University Institute for Neurological Sciences, and the Department of Neurosurgery at Acibadem Hospital between 1987 and 2006. A pterional approach was used in all cases. Findings. The mean tumour volume was 34.2 +/- 46.6 cc. Sixteen (37.2%) of the tumours were giant (largest diameter > 4 cm). Total surgical removal was achieved in 39 cases (90.7%) and subtotal removal in 4 cases (9.3%). Eight patients (18.6%) developed early postoperative complications. The median and range of follow-up time was 39, R = 99 (3, 102) months. Four (9.3%) of the 43 tumours recurred during follow-up and were treated with radiosurgery. Conclusion. Anterior clinoidal meningioma is a separate disease entity from other meningiomas of the medial third of the sphenoid wing. Relatively good outcomes can be stated in this specific subgroup if growth criteria competable with true diagnosis are fulfilled. Size should be incorporated into any classification scheme for determining clinical and surgical risk. The standard pterional approach is sufficient for removing anterior clinoidal meningiomas.
Keywords: classification; clinoidal; meningioma; sphenoid wing; surgery; GAMMA-KNIFE RADIOSURGERY; TUBERCULUM SELLAE MENINGIOMAS; SKULL BASE MENINGIOMAS; PTERIONAL SURGERY; MANAGEMENT; RECURRENCE; EXPERIENCE